Antimicrobial activity of polyphenol-rich fractions from Sida alba L. (Malvaceae) against co-trimoxazol-resistant bacteria strains - Konaté Kiessoun; Hilou Adama; Mavoungou Jacques; Lepengué Alexis; Souza Alain; Barro Nicolas; Datté Jacques Y; M'Batchi Bertrand; Nacoulma Odile (BMC, 2012)
Abstract Background The increased resistance of microorganisms to the currently used antimicrobials has lead to the evaluation of other agents that might have antimicrobial activity. Medicinal plants are sources of phytochemicals which are able to initiate different biological activities including antimicrobials Materials and methods In vitro antibacterial (MIC, MBC and time-kill studies) of polyphenol-rich fractions from Sida alba L. (Malvaceae) was assessed using ten bacteria strains (Gram-negative and Gram-positive). Results All test bacteria were susceptible to the polyphenol-rich fractions. Time-kill results showed that after 5 h exposition there was no viable microorganism in the initial inoculum and the effect of polyphenol-rich fractions was faster on Enterococcus faecalis (Gram-positive bacterium) comparatively to the other bacteria strains. Conclusion The data analysis indicates that the tested of polyphenol-rich fractions has significant effects when compared with the standard antibiotic. These results therefore justify the traditional use of sida alba L., alone or in combination with other herbs to treat bacterial infections.